Insulin-like growth factors and cancer from basic biology to therapeutics - LeRoith, Derek (Cancer drug discovery and development,, 2012)
The insulin-like growth factor system has been shown to play a critical role in cancer development and progression. Insulin-like Growth Factors and Cancer: From Basic Biology to Therapeutics, specifically brings these aspects to the reader. The volume covers the epidemiological aspects of the relationships between circulating insulin and IGF-1 levels and the risk for cancer and cancer-related mortality and in particularly in disease states such as obesity and Type 2 diabetes. It then addresses the basic biology of the system and how the ligands, receptors and IGF-binding proteins affect cancer cell biology and cancer progression. Finally, it discusses the therapeutic potential of inhibiting the receptors using various newly discovered monoclonal antibodies and tyrosine kinase inhibitors that are in preclinical and clinical trials. Preface -- Epidemiology of IGF-1 and Cancer -- Aging and Cancer: The IGF-I Connection -- Obesity, Type 2 Diabetes and Cancer -- IGF System and Breast Cancer -- The Role of Insulin-Like Growth Factor Signaling in Prostate Cancer Development and Progression -- Mouse Models of IGF-1 Deficiency -- Insulin-like Growth Factor Signaling in Pediatric Sarcomas -- Cancer Genes, Tumor Suppressors, and Regulation of IGF-1R Expression in Cancer -- Mouse Models of IGF-1R and Cancer -- Targeting the Insulin-Like Growth Factor-I Receptor in Cancer Therapy -- Targeting Insulin-like Growth Factor (IGF-1R) and Insulin Receptor Signaling by Tyrosine Kinase Inhibitors in Cancer -- Calories and Cancer:  The Role of Insulin-like Growth Factor -- Cancer Cell Metabolism -- Overlaps between the Insulin and IGF-1R and Cancer -- Index.